2019
DOI: 10.11591/ijece.v9i3.pp1968-1977
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent black hole detection in mobile AdHoc networks

Abstract: <div class="WordSection1"><p>Security is a critical and challenging issue in MANET due to its open-nature characteristics such as: mobility, wireless communications, self-organizing and dynamic topology. MANETs are commonly the target of black hole attacks. These are launched by malicious nodes that join the network to sabotage and drain it of its resources. Black hole nodes intercept exchanged data packets and simply drop them. The black hole node uses vulnerabilities in the routing protocol of MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…They used trust and authentication (using asymmetric encryption) to secure data. In [26] as well, two secure routing methods named binary decision diagram AODV was proposed for MANET's security. To improve security, authors suggested multipath transmission in MANETs.…”
Section: Related Workmentioning
confidence: 99%
“…They used trust and authentication (using asymmetric encryption) to secure data. In [26] as well, two secure routing methods named binary decision diagram AODV was proposed for MANET's security. To improve security, authors suggested multipath transmission in MANETs.…”
Section: Related Workmentioning
confidence: 99%
“…Neighbor m = node updates their routing table and creates a blacklist for blackhole node which will be ignored in the future routing. Khamayseh et al 57 proposed two secure routing protocols (e.g. binary decision diagram AODV (BDD-AODV) and Hybrid).…”
Section: Related Workmentioning
confidence: 99%
“…In turn, geospatial tools such as the Global Navigation and Global Positioning System in precision agriculture even the satellite network (GNSS) will play an important role as they can indicate any component's exact position. Wireless sensor network (WSN) [1] [2] and AdHoc Network [3] [44], especially FANET (Flying AdHoc Network) [20], a new form of Mobile Ad Hoc Network (MANET) [45] is one of the efficient platforms which we can apply for betterment of agriculture. The increase in the production of UAVs [33] is also a very promising approach for the collection of realtime details, as it is considered as one of the most ambitious precision-farming technologies [46] [47].…”
Section: Introductionmentioning
confidence: 99%